Kebijakan pemisahan tempat duduk moda transportasi umum dalam perspektif gender (Studi kasus pengguna bus Transjateng jalur Purwokerto-Purbalingga) - A. Luthfi Hamidi; Anggitiyas Sekarinasih; Endang Sartika; Hendri Purbo Waseso (Yinyang: Jurnal Studi Islam Gender dan Anak, 2023)
This study aims to find the formulation of the policy of separation of seats in a gender perspective on the Trans Jateng Barlingmascakeb Bus Corridor I Purwokerto-Purbalingga. This field research used documentation, observation, interview and questionnaire techniques in the collection of data and then analyzed qualitatively by describing narratively the results of the analysis found. The results of this research are (1) the policy of separation of seats in the Central Java Trans Barlingmascakeb Bus Corridor I Purwokerto-Purbalingga is a formal policy in the form of an oral regulation because there are no documents that specifically explain it; (2) The policy of separation of seats or gender segregation is applied by the Central Java Transportation Office as a preventive measure for crimes such as sexual harassment; and (3) The application of the seat separation policy on the Trans Jateng Barlingmascakeb Bus Corridor I Purwokerto-Purbalingga is not yet effective. This is indicated by the disproportionate seating between men and women resulting in the non-compliance of users to occupy seats according to sex.